A Review of PSD and Soil Classification of DMS: Characterization and Challenges - SM Johan, Siti Farhanah; Chan, Chee-Ming; Sarani, Noor Amira; M.Sa’don, Norazzlina; Mohamed Sutan, Norsuzailina; Abdul Karim, Abdul Razak; Redzuan, Faisal Amsyar (Journal of Soil, Environment & Agroecology, 2025)
Dredged Marine Soils (DMS) are variable sediments excavated for navigation and development. Initially poor in geotechnical quality, their composition reflects diverse geological and anthropogenic influences. While Particle Size Distribution (PSD) analysis and the Unified Soil Classification System (USCS) are standard tools, DMS heterogeneity, including organic matter and debris, limits their effectiveness. Dredging and pre-treatment also alter PSD. The USCS, designed for more homogeneous soils, struggles to accurately classify complex DMS mixtures, hindering predictive capability for engineering behavior. Challenges in sampling and testing further complicated characterization. Effective beneficial reuse requires moving beyond traditional classification towards comprehensive, performance-based evaluations and site-specific investigations to fully understand and utilize these complex materials.